Analisis Investasi Rekayasa Proyek Pembangunan RS PTN Universitas Lampung - Ambarwati, Anissa Putri; Kustiani, Ika; Widyawati, Ratna (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The establishment of RS PTN Unila is intended to fulfill social function by provided health services as well as income generating unit. RS PTN Unila is also expected to be a center of collaboration between research and health services. Even though the facility is provided by government of the province of lampung, The study was carried out to examine the viability of the invested. The viability was analyzed through several parameter, named Net Present Value (NPV), Benefit to Cost Ratio (BCR), Internal Rate of Return (IRR), Payback Period (PP).The viability was also analyzed through 9 scenarios. Scenarios were varied base on inflation rate and Bed occupancy rate. The result show that all scenarions was viable. The best scenarions was based on the assumptions of bed occupancy rate 100%, inflation rate of 5 % and discount rate 15% and the source of investment provided by government. Keyword: Feasibility Study , Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), Payback Period (PP)